Cholinesterase inhibitor rivastigmine enhances nerve growth factor-induced neurite outgrowth in PC12 cells via sigma-1 and sigma-2 receptors - Terada, Kazuki (PLoS One, 2018)
Rivastigmine (Riv) is a potent and selective cholinesterase (acetylcholinesterase, AChE and butyrylcholinesterase, BuChE) inhibitor developed for the treatment of Alzheimer’s disease (AD). To elucidate whether Riv causes neuronal differentiation, we examined its effect on nerve growth factor (NGF)-induced neurite outgrowth in PC12 cells. At concentrations of 0–100 μM, Riv was non-toxic in PC12 cells. Riv caused dose-dependent (10–100 μM) enhancement of NGF-induced neurite outgrowth, which was completely inhibited by the TrkA antagonist GW-441756. By contrast, Riv-mediated enhancement of neurite outgrowth was not blocked by the acetylcholine receptor antagonists, scopolamine and hexamethonium. However, the sigma-1 receptor (Sig-1R) antagonist NE-100 and sigma-2 receptor (Sig-2R) antagonist SM-21 each blocked about half of the Riv-mediated enhancement of NGF-induced neurite outgrowth. Interestingly, the simultaneous application of NE-100 and SM-21 completely blocked the enhancement of NGF-induced neurite outgrowth by Riv. These findings suggest that both Sig-1R and Sig-2R play important roles in NGF-induced neurite outgrowth through TrkA and that Riv may contribute to neuronal repair via Sig-1R and Sig-2R in AD therapy.